Door but not four and 4 a category specific transcoding deficit in a pure acalculic patient. - Denes, G; Signorini, M (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 2001)
We report a left parietal damaged, acalculic, non aphasic patient who showed a specific deficit in reading Arabic and spelled-out numerals. Word reading was flawless, while he showed a severe impairment in reading meaningless strings of phonemes (phonological alexia). He also showed a dissociation between the preserved ability to retrieve knowledge about general facts and the impairment in retrieving cardinal, personal and non-personal numerical facts. These findings point to a separate organization in the brain of the numerical domain.